Freeze-drying for microencapsulation of turmeric oleoresin using modified starch and gelatin - Mayer, Cassia Roberta Malacrida [UNESP]; Ferreira, Sungil [UNESP]; Zuanon, Larissa Angélica Cirelli [UNESP]; Telis, Vânia Regina Nicoletti [UNESP] (Hindawi, 2014)
The aims of this study were to assess the turmeric oleoresin microencapsulation by freeze-drying with modified starch/gelatin and to evaluate its stability during storage at different temperatures and light. Encapsulated turmeric oleoresin w stored at −20, 25 and 60C, in the absence of light, and at 25C in the presence of light, and analyzed over a period of 6 weeks for curcumin and total phenolic contents and color. The different concentrations of wall material showed no significant effect on the curcumin retention. The best conditions for microencapsulation of turmeric oleoresin were: wall material composed of 30 g/100 g of modified starch + 1 g/100 g gelatin and mechanical homogenization. Encapsulated material was more stable during storage at −20C and less stable at 25C in the presence of light.